Impact Of Tourism On Community Development And Income In Kuta Mandalika Beach Kuta Village, Pujut District, Central Lombok - Haris, Abdul; Ningsih, Nurul Hidayati Indra (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2020)
Tourism is one of the sectors that provides the largest contribution to national economic growth so the government pays special attention to its development. One form of tourism development program in West Nusa Tenggara Province is the development of Kuta Beach as one of the Mandalika Special Economic Zones (KEK). The development of tourism has an impact or influence on the community around the area. The research problem is formulated as follows: How is the impact of tourism on community development in Kuta Mandalika Beach Kuta Village, Pujut District, Central Lombok? 2) What is the impact of tourism on community income in Kuta Mandalika Beach, Kuta Village, Pujut District, Central Lombok? This research is a qualitative descriptive study with data collection techniques in the form of interviews, observations, and documentation. This study describes the development of tourism by examining a group of people, namely groups of tourism businesses in the vicinity of the Mandalika Kuta Beach Area. The aim is to find out whether there are changes that occur in terms of community development in the economic, socio-cultural, environmental and community income from tourism development. The results showed that tourism had an impact on community development in Kuta Mandalika Beach, Kuta Village, Pujut District, especially in the economic, social cultural and environmental fields. In addition, tourism also impacts on people's income through increased business capacity in the tourism sector, such as hotels, restaurants, tour guides, travel agencies, shops and tourism service businesses, but it has a decreased impact on business capacity for craft / artshop tourism businesses, hawkers / Street vendor.